(untitled) (Al-Academy, 2017)
The deliberative system of communicative studies is exposed to cultural openness, according to modern cultural studies, to establish a verbal language system that achieves reciprocal and cross-cultural relations. This research has examined the concept of deliberative approach in the contemporary Iraqi theater text by studying the deliberative system of text and its interrelationship with The stage of the verbal embodiment of the dramatic event, because the dramatic text achieves in its construction of racism, a deliberative approach between the verbal event and the language, and what later leads to the completion of the dramatic action. The research included four chapters. The first chapter was the systematic framework of the research, The problem of research and the need for automation, and the importance of research and its limits. The second chapter included the first topic (approach to deliberation - concept and rationale) and the second topic (Representations of approach to deliberation in the text of the world theater) The third chapter was adopted analysis of the sample of the elected research (mouths) of the writer Abdul Hussein Mahood. And chapter IV, which included findings, conclusions and a list of resource margins